PENGARUH STRUKTUR KEPEMILIKAN SAHAM OLEH PEMERINTAH DAERAH, TOTAL KREDIT, DAN KOMPLEKSITAS USAHA TERHADAP BIAYA MONITORING BPD SE INDONESIA - Bambang Bambang; RR. Sri Pancawati; Biana Adha Inapty; Iwan Kusuma Negara (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2018)
This study aims to determine the effect of capital structure, credit, and business complexity on monitoring costs performed on 21 BPD in Indonesia. The statistical test results show that the local government ownership has no influence on monitoring costs. These results may confirm the effectiveness of the supervisory authority to the Bank in form of who eligible to be commissioner and the minimum shares must to paid as risk buffer. The amount of credit provided by the bank has an effect on monitoring cost which can be interpreted that the supervision of the bank's main activity is supervision of earning assets conducted in line with credit changes. Similarly, the business complexity of BPD influences the cost of monitoring BPD Se Indonesia. The duties of the Board of Commissioners are also expected to make visits to branches of banks scattered in the work area and outside the region in order to conduct active supervision and provide motivation and advisory to all levels in BPD. This function are expeceted for small size of BPD.